Development and application of a mathematical model for evaluating extra energy cost due to disproportional energy consumption - Oke, Sunday Ayoola; Oyedokun, Oluwafemi Isaac (Journal of Business Economics and Management, 2007)
In this investigation, a scientific approach is presented in quantifying energy losses associated with production facilities. The corresponding analytical approach in estimating energy requirement of equipment is shown. In particular, mathematical information on how extra energy cost due to extra energy losses that occur in equipment is measured has been shown. The premise of the study is based on the fact that the value of the efficiency of the equipment determines the value of the energy that can be lost for a time frame. Similarly, the heat generated in some equipment, like lamps and air conditioner, can constitute energy lost in equipment. The paper then further shows that the energy cost paid for the energy losses that occur in equipment can be determined by using the energy cost rate used for calculating the cost paid for the useful work done. As manufacturing companies strive to meet and exceed the expected needs of the customer with cost saving manufacturing processes, a major hurdle is the losses in energy transfer as a result of inefficiencies in operations. This paper is geared towards achieving effective and efficient manufacturing processes by researching into trends in energy losses. The results obtained show the feasibility of the applied procedure. There is no previous documentation that has addressed the current problem using the approach presented. This is therefore a new way of viewing energy consumption.First Published Online: 14 Oct 2010